The investigation of the fatigue failure of nickel-based superalloy 718 choke valve stems used in offshore subsea water injection service. (March 2020) - Ejaz, Muhammad; Mahmoud, Essam R.I.; Khan, Sohaib Z.
Highlights: Two choke valve inserts manufactured from 718 Ni superalloys were fractured in offshore field service. The materials and mechanical properties were correct and complied with API 6A718. The diagnose shows that fatigue was the primary failure mechanism. Fatigue was initiated at a high local tensile stress concentration at pressure balancing holes. The main drive of fatigue crack propagation was the high-low-stress cycles. Abstract: This paper analyse the failure of two choke valve inserts from offshore subsea service in the Northern North Sea. The choke valve stems were manufactured from Nickel-based superalloys 718 and coated with WC. The design life was 25 years. Treated seawater was injected at a rate of 5600 m 3 /d for about 3 years, and then water injection rate was increased to 7360 m 3 /d in next 4 years with an addition of produced water from the field. Maximum design flowrate for the choke was 8320 m 3 /d. The first choke was failed after about 7 years in operation. The choke was removed and replaced by a second choke of same design and material of construction, which failed after less than 12 months service. The failure occurred almost at the same location at the hollow stem section where pressure balancing port holes were drilled. The analyses were concentrated on the fractography as well as materials chemical, mechanical and metallurgical evaluation. All the materials examination demonstrated that the failed stem material complied with API 6A718 and had been heat-treated correctly. The diagnose shows that fatigue was the primary failure mechanism. Fatigue initiation occurred at a location on a port owing to particularly high local tensile stress concentration. The main drive of fatigue crack initiation and propagation, in this case, appears to be the loading cycle. Fractography (beach marks) indicated that high frequency low amplitude fatigue mechanism was active. The balance port is recommended to be moved to the top of plug where local tensile stress concentration is inticepated to be minimum.